Back to the future? Chinese artistic tradition and topologies of urban modernity. (1st September 2019) - Becher, Angela
AbstractThe radical nature of China's urban transformation has become a key subject in contemporary Chinese art. The ruthless eradication of material remnants of the past, moreover, has reinvigorated an urgency in Chinese art to look to the past for inspiration in the envisioning of a better future. This article examines three works that combine these two important strands of artistic production in China as they negotiate contemporary urban transformation via a return to China´s artistic tradition. This article will look at the imaginary and fantastical topologies of modernity in both analogue and new media, including the installation and oil painting of Shen Yuan and Wang Mingxian, respectively, and the digital ink painting of Miao Xiaochun. In examining closely the artists' choices of medium and their representations of architecture and urban space, this article probes some of the key social, environmental and aesthetic predicaments that underlie China's developmental process. It will argue that responses in Chinese art counter the officially sanctioned grand narrative that equates urbanization, urban renewal and modernization with unequivocal social betterment. Instead, these works create in-between spaces that lie between the material and the idealistic.